Knowledge on dental trauma and orthodontic tooth movement held by a group of orthodontists - Pedro Marcelo Tondelli; Marcos Rogério de Mendonça; Osmar Aparecido Cuoghi; Alex Luiz Pozzobon Pereira; Mauro Carlos Agner Busato (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The objective of this work was to assess the knowledge about orthodontic tooth movement and dental trauma held by a group of orthodontists in specific areas of Brazil. For this purpose, 166 questionnaires with 15 objective questions about this subject were distributed. One hundred and five questionnaires were properly filled and collected after 30 days. It was concluded that, except for avulsion, the knowledge on dental injuries held by the professionals interviewed was considered unsatisfactory, and about 40% of them were not acquainted with the recommendations for the orthodontic movement of traumatized teeth.